Flexible and stable three-layer porous structure hemostatic dressing and preparation method thereof
By using gelatin, hydroxyethyl cellulose, carboxymethyl chitosan, sodium alginate and tannic acid in the hemostatic dressing, a three-layer double-network porous structure is formed, which solves the single function and biodegradation of the existing hemostatic dressing. The problem of insufficient ability achieves stability and rapid hemostasis in dry and wet environments, and reduces damage to wounds.
Patent Information
- Application Number
- CN202411218921.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-10
AI Technical Summary
The existing hemostatic dressing has a single function and insufficient biodegradation ability, resulting in frequent replacements that increase treatment costs and secondary damage to the wound. It is poor in dry and wet environments, making it difficult to achieve rapid hemostatic and long-term preservation.
Using gelatin and hydroxyethyl cellulose as the basic skeleton, combining carboxymethyl chitosan, sodium alginate and tannin, the design of a double-layer asymmetric polysaccharide porous structure and cotton gauze is formed to form a three-layer double-network porous structure. , realize a stable foaming system and cross-linking process, reduce storage difficulty and enhance antioxidant and antibacterial properties.
It realizes flexible and stable cutting in dry and wet environments, has excellent water vapor transmission, antibacterial activity and hemostatic properties, reduces damage to wounds, and can be preserved for a long time, which is significantly better than commercially available hemostatic gauze and gelatin to stop bleeding. sponge.
Smart Images

Figure CN119280455A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible and stable three-layer porous structure hemostatic dressing and a preparation method thereof, belonging to the technical field of biomedicine. Background Art
[0002] Most porous structures in nature are multi-layered and internally integrated. To a certain extent, they can produce higher efficiency and some special properties, thereby changing the material structure and making an indelible contribution to expanding and promoting functional applications. However, research on this structure in the biomedical field is far from enough. Existing wound dressings have a single function and insufficient biodegradability, requiring frequent replacement of wound dressings, which will increase treatment costs and cause patients to suffer more pain. In addition, the rich functions of dressings may invisibly increase manufacturing costs and process difficulty in actual industrial production.
[0003] Therefore, how to reduce the process steps, realize integrated production, improve the performance and function of hemostatic dressings and quickly achieve biodegradation, avoid secondary damage to the wound caused by changing dressings, and at the same time achieve mechanical properties suitable for wound recovery, rapid hemostatic properties and long-term and simple storage methods has become a technology that urgently needs to be considered.
[0004] Various new functional dressings tailored for moist and dynamic environments have attracted extensive attention. In order to accelerate and improve wound healing and achieve better wound care, ideal wound dressings should have key properties such as biocompatibility, protection, isolation, wet adhesion, convenience, stability, easy removal and deformability. Researchers have been pursuing lightweight, durable and multifunctional biodegradable dressings.
[0005] Constructing stable porous structures with environmentally friendly, renewable, and low-toxic materials has become a key step. Natural proteins and polysaccharides and their derivatives, such as gelatin, sodium alginate, carboxymethyl chitosan, and hydroxyethyl cellulose, are given priority due to their unique properties, including low antigenicity, high biodegradability, biocompatibility, and promotion of cell growth. Gelatin and other biomolecules are interconnected by electrostatic forces, hydrogen bonds, hydrophobic or van der Waals interactions to form gelatin / macromolecular aggregates with different properties. At the same time, continuous research has focused on the extraction and utilization of natural plant extracts, such as tannic acid, as excellent natural functional agents with significant and irreplaceable advantages. The versatility of tannic acid in interacting with proteins and its potential application in the manufacture of complex biomaterials make it an important contributor to the structure of dressings.
[0006] For example, Chinese patent CN202210220719.0 discloses a rapid hemostatic sponge, whose components include gelatin, a polysaccharide complex and a cross-linking agent. The polysaccharide complex is obtained by physically cross-linking a hydrophobic modified polysaccharide complex and a hydrophilic modified polysaccharide complex; however, its structure is single and the functions obtained are also relatively single.
[0007] Chinese patent CN202310442095.1 discloses a method for preparing a self-healing antibacterial and analgesic gelatin hydrogel wound dressing and its application. The preparation of the hydrogel wound dressing is to oxidize the phenolic group of tannic acid to a quinone group by blowing air, and then react with the amino group of gelatin to obtain a tannic acid-gelatin hydrogel precursor solution, and then react with β-cyclodextrin tetracaine inclusion complex to obtain a self-healing antibacterial and analgesic gelatin hydrogel wound dressing. The dressing can provide a moist wound environment, has excellent self-healing properties, excellent antibacterial properties, and a long sustained release time of the drug, which promotes wound healing while relieving pain, but the liquid contained in the hydrogel is relatively fixed, and the structure is single, and the functional regulation ability is poor.
[0008] In addition, Chinese patent CN202410032205.1 discloses a hemostatic gauze and a preparation method thereof, comprising the following components by weight: 10-20 parts of graphene oxide, 20-30 parts of chitosan-silicone rubber copolymer, 10-15 parts of polyethylene oxide, and 50-60 parts of non-woven fabric; graphene oxide, chitosan-silicone rubber copolymer, and polyethylene oxide are coated on the non-woven fabric according to the ratio, heated, and then pressed to obtain hemostatic gauze; it has good antibacterial and hemostatic effects; at the same time, the operation process is simple, the production cost is low, and it is suitable for large-scale production; but its structure is single and the functions obtained are also relatively single. Summary of the invention
[0009] In view of the defects and shortcomings of the prior art, the present invention provides a flexible and stable three-layer porous hemostatic dressing and a preparation method thereof. The large-area hemostatic dressing prepared by this method can be arbitrarily cut in a dry or wet environment, has a differentiated double network structure, has good water vapor permeability, and strong antioxidant and antibacterial properties, thereby achieving rapid hemostasis.
[0010] Specifically, gelatin and hydroxyethyl cellulose are used as the basic skeleton material, and as active agents to create a stable foaming system for carboxymethyl chitosan, sodium alginate and tannic acid to prepare a double-layer asymmetric polysaccharide-based porous structure. Through the different design structures of cotton gauze, the two substrates complement each other and benefit each other. This reduces the preparation steps and simplifies the process. In the preparation process, the impregnation solution becomes weakly acidic due to the release of rich tannic acid in the sample, which promotes the reaction of sodium alginate and Ca 2+Cross-linking makes the dressing soft and elastic, combining the advantages of both the inside and outside gel methods. The resulting sample can absorb moisture quickly and maintain structural integrity when used in a liquid environment, reducing the difficulty of preservation, achieving the diversity of medical dressing structure and function, and can be preserved for a long time.
[0011] The first object of the present invention is to provide a method for preparing a flexible and stable three-layer porous hemostatic dressing, the preparation method comprising the following steps:
[0012] (1) preparing a mixed aqueous solution using protein substances and cellulose derivative substances as solutes and water as solvent;
[0013] (2) adding glycerol to the mixed aqueous solution obtained in step (1), stirring at high speed until the volume of the solution foams, and the volume after foaming reaches 1.5 to 3 times of the original volume, and stopping when stability is reached, thereby forming a foaming solution A;
[0014] (3) using a polysaccharide-based matrix material as a solute, water as a solvent, and adding glycerol to prepare solution B;
[0015] (4) adding the solution B of step (3) to the foaming solution A obtained in step (2) to obtain a mixed solution C, stirring at high speed, and then adding tannic acid to form a mixed solution D, and continuing to stir at high speed to obtain a double-layer solution;
[0016] (5) Product structure design: Pour the lower layer of the double-layer solution in step (4) onto a culture dish, then spread the cotton gauze on it, and then pour the upper layer of the double-layer solution in step (4) onto the cotton gauze, forming a U (upper layer of solution)-C (cotton gauze)-L (lower layer of solution) structure (UCL) from top to bottom;
[0017] (6) freezing the product obtained in step (5) immediately, freeze-drying it, and then placing it in an impregnation solution for impregnation cross-linking;
[0018] (7) The cross-linked product obtained in step (6) is washed and freeze-dried again to obtain a flexible and stable three-layer porous hemostatic dressing.
[0019] In one embodiment, the protein substance in step (1) includes one or more of egg white, gelatin, collagen, and protein powder; and the cellulose derivatives include one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
[0020] In one embodiment, the mass concentrations of proteins and cellulose derivatives in the mixed aqueous solution of step (1) are 0.5wt% to 5wt% and 0.5wt% to 5wt%, respectively; more preferably, they are 2 to 5wt% and 1.5 to 3wt%, respectively.
[0021] In one embodiment, the glycerol content in solution A in step (2) is 0.1 to 5 wt %, preferably 1 to 3 wt %.
[0022] In one embodiment, the high-speed stirring speed of step (2) is 0.5-15K rpm, and the time is 1-60 minutes; preferably, the stirring speed is 10-15K rpm, and the time is 4-10 minutes.
[0023] In one embodiment, the polysaccharide-based matrix material in step (3) includes one or more of chitin, chitosan, carboxymethyl chitosan, cellulose, sodium carboxymethyl cellulose, sodium alginate, starch, agar, pectin and gum, and glycosaminoglycan.
[0024] In one embodiment, the polysaccharide content in solution B of step (3) is 1 wt% to 5 wt%, preferably 2 to 5 wt%, and the glycerol content is 0.1 to 5 wt%, preferably 2 to 4 wt%.
[0025] In one embodiment, the polysaccharide-based matrix material in step (3) is carboxymethyl chitosan and sodium alginate, wherein the polysaccharide content in solution B is 2.5 wt %, and the mass ratio of carboxymethyl chitosan to sodium alginate is 3:1.
[0026] In one embodiment, the concentration of tannic acid added to solution D in step (4) is 0-1.5wt%; preferably 0.5-1wt%; further preferably 0wt%, 0.25wt%, 0.5wt%, 0.75wt%, 1wt%, 1.25wt%, 1.5wt%.
[0027] In one embodiment, the volume ratio of the foaming solution A to the solution B in step (4) is 3:1 to 1:3; preferably 2:1.
[0028] In one embodiment, the high-speed stirring speed of step (4) is 0.5-15K rpm, and the time is 1-60 minutes; preferably, the stirring speed is 15K rpm, and the time is 3 minutes.
[0029] In one embodiment, the cotton gauze in step (5) is cotton gauze that has been ultrasonically cleaned and dried and then ultrasonically immersed in a tannic acid solution and then frozen.
[0030] In one embodiment, the ultrasonic cleaning time is 0.5 to 2 hours, preferably 1 hour; the tannic acid solution is a tannic acid aqueous solution with a concentration of 0 to 1.5 wt%; the total ultrasonic immersion time in the tannic acid solution is 1 to 48 hours; further preferably, ultrasonic immersion is first performed for 1 hour and then for 24 hours.
[0031] In one embodiment, the freezing refers to laying the impregnated cotton gauze flat and then freezing it in a -80°C ultra-low temperature refrigerator, and the freezing time is 5 to 60 minutes, preferably 10 minutes.
[0032] In one embodiment, the concentration of the tannic acid solution used for impregnation of the cotton gauze is the same as the concentration of the tannic acid solution in step (4).
[0033] In one embodiment, the composition of the impregnation solution in step (6) is: an aqueous solution of 0.1 mol / LCaCl2 and 2 wt% glycerol;
[0034] In one embodiment, the cross-linking time in step (6) is 3 to 5 minutes, preferably 5 minutes.
[0035] In one embodiment, the freezing conditions of steps (6) and (7) are: freezing in an ultra-low temperature refrigerator at -80 to -60°C, and freeze-drying for 36 to 48 hours; preferably, freezing in an ultra-low temperature refrigerator at -80°C, and freeze-drying for 36 hours.
[0036] The second object of the present invention is to provide a flexible and stable three-layer porous hemostatic dressing based on gelatin and multi-source polysaccharide reinforced cross-linked cotton yarn fabric prepared by the above method.
[0037] In one embodiment, the hemostatic dressing is an integrally formed three-layer double-network porous structure in a three-dimensional mesh structure, which combines the advantages of a porous structure and cotton gauze, enriches the structure and improves the structural stability of large-area dressings.
[0038] Beneficial effects of the present invention:
[0039] (1) The present invention uses protein and polysaccharide to construct a stable foaming system, and combines multi-source polysaccharide and tannic acid to construct a double three-dimensional network. After being superimposed with cotton gauze to design a large-area dressing structure, the Ca 2+An integrated three-layer double-network multi-source porous structure dressing is prepared by cross-linking impregnation and freeze-drying; the swelling morphology of the porous structure in the outer layer of the dressing is adjusted to the optimal state by optimizing the dosage ratio of raw materials, process parameters and preparation steps, and a low-toxic dressing with excellent water vapor permeability, antibacterial activity, antioxidant activity and hemostatic performance is obtained: the dressing has a three-layer double porous structure, each layer has a different structure, the dressing has good flexibility, water retention and air permeability, and has good shape retention and recovery capabilities; it can quickly absorb blood and tissue fluid around the wound, has an extremely fast hemostatic effect and reduces bleeding, can effectively maintain the moisture of the wound, has extremely fast and excellent antioxidant properties, avoids bacterial invasion and infection, and can quickly and effectively kill bacteria; it has a promoting effect on the later recovery of the wound; excellent biocompatibility and biodegradability can reduce the number of changes and effectively reduce the damage to the new granulation tissue in the wound; at the same time, it combines the advantages of porous structure and cotton gauze, enriches the structure and improves the structural stability of large-area dressings. The above characteristics can be maintained after long-term storage at room temperature; its basic physical properties meet the requirements of medical dressings;
[0040] (2) Compared with the existing dressing preparation process, the hemostatic dressing of the present invention has the characteristics of internal structural integration and better repeatability. The three-layer structure of the present invention (high-speed homogeneous foaming in the foaming system of protein and polysaccharide followed by static stratification) and the double network structure (multiple source polysaccharides in the weakly acidic Ca2+ / -2-hydroxy-2-carbon tannic acid environment) are 2+ The composition of the present invention is that the tannic acid and the dressing are combined to form a more stable structure, and the dressing can maintain excellent bending performance in both dry and wet states, and can achieve rapid anti-oxidation, antibacterial and hemostatic functions, and has good biocompatibility. At the same time, the preparation method of the present invention is more convenient, and can achieve rapid hemostatic performance, which is significantly better than commercially available hemostatic gauze and commercially available gelatin hemostatic sponge, that is, the performance is more excellent and the cost is lower.
[0041] (3) Tannic acid in the present invention is used as the main cross-linking agent and functional agent to enhance the binding force between protein and polysaccharide groups to form a first network structure, and endow the dressing with antibacterial and antioxidant functions, while promoting hemostasis; through the weakly acidic Ca 2+ Cross-linking gives the dressing a second structure, which strengthens the stability of the dressing structure and enhances the resilience of the dressing, making the dressing structure less likely to disperse in a humid environment and more adherent to the human epidermis in a wet environment.
[0042] (4) The three-layer porous structure hemostatic dressing based on gelatin and multi-source polysaccharide reinforced cross-linked cotton yarn fabric prepared by the present invention is flexible and stable and can be cut at will in dry or wet environments. It has various excellent properties and is better than commercially available hemostatic dressings. It overcomes the preparation area limitation of the porous structure and improves the single structure and functionality of the cotton gauze. It combines the advantages of the two, takes their strengths and makes up for their weaknesses, and benefits each other. It can be sealed and stored at room temperature for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The surface morphology of cotton gauze before and after treatment, SEM images of hemostatic dressing samples prepared in Examples 1 to 6 and Comparative Example 1: a is the original cotton gauze, b is the cotton gauze after ultrasonic cleaning, and c is the cotton gauze after ultrasonic immersion treatment in tannic acid solution; m, n, o are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Example 1; d, e, f are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Comparative Example 1; g, h, i are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Example 2 The upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer; j, k, l are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Example 3; p, q, r are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Example 4; s, t, u are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Example 5; v, w, x are the upper porous structure layer, the lower porous structure layer and the middle cotton gauze layer of Example 1;
[0044] Figure 2 The following are actual pictures of the hemostatic dressings prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0045] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0046] The test method involved in the present invention is:
[0047] 1. Calculation of porosity
[0048] According to the formula:
[0049]
[0050]
[0051] According to this calculation, in the formula, m (g) and V (cm 3 ) represents the weight and volume of the sample; w G ,w H ,w C and w S are the added proportions of gelatin, hydroxyethyl cellulose, carboxymethyl chitosan and sodium alginate in the dry sample; ρ G ,ρ H ,ρ C and ρ SThe skeleton densities of gelatin, hydroxyethyl cellulose, carboxymethyl chitosan and sodium alginate are 1.04, 0.75, 1.60 and 1.00 g / cm, respectively. 3 .
[0052] 2. Test method for water vapor transmission rate
[0053] The water vapor permeability of the dressing samples prepared in the examples and comparative examples was tested according to GB 1037-88 "Test method for water vapor permeability of plastic films and sheets - cup method". All samples (round, 1.2 cm in diameter, 1.0 mm in thickness) were sealed in a centrifuge tube containing 2 ml of deionized water and stored at 37°C and 75% humidity for 24 hours before testing. Then, the mass loss of water in the centrifuge tube was measured and the mass loss was calculated according to the formula Calculate, where A, W2, and W1 are the centrifuge orifice areas (m 2 ), initial weight of the centrifuge tube containing water (g), weight of the centrifuge tube containing water after 24h (g).
[0054] 3. In vitro degradation test methods
[0055] The samples to be tested were cultured in phosphate buffered saline (PBS, pH 7.4) containing lysozyme (10 ku / mL) at 37°C. All samples were taken out at fixed time intervals, dried, and weighed. Each group was repeated 3 times. The mixture was centrifuged to separate the residue, and then freeze-dried and weighed to obtain the precipitate. The degradation rate was expressed as the weight loss rate, and the weight loss rate was calculated by the formula:
[0056] Wherein W7 and W6 are the initial weight and dry weight of the residue after degradation of each sample, respectively.
[0057] 4. Test methods for antioxidant properties
[0058] Different samples were immersed in anhydrous ethanol for 2 hours and 24 hours to obtain 10 mg / mL immersion solutions. Then the liquid (control group: anhydrous ethanol as blank sample) and an equal amount of DPPH solution (40 μg / mL) were placed in a microplate reader for reaction. The scavenging activity of the sample on stable DPPH was then measured at 516 nm. In the dark, DPPH reacted with antioxidant compounds and was reduced. Calculate, where A0 and A s They are the absorption of blank sample (t=0min) and tested solution respectively.
[0059] 5. Antimicrobial testing methods
[0060] The antibacterial properties of the dressing samples prepared in each embodiment and comparative example were tested according to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method". All antibacterial tests were carried out in a sterile environment, and all samples were sterilized by ultraviolet light. Staphylococcus aureus (S. aureus, ATCC 6538) and Escherichia coli (E. coli, ATCC 8739) were used as representatives of Gram-positive bacteria and Gram-negative bacteria, respectively, to calculate the antibacterial activity of the samples. The initial concentration of the bacterial suspension was 1 to 5 × 10 9 CFU / mL. The blank group without sample was used as a reference for antibacterial effect. All test samples (sterilized, 0.75g±0.05g) were placed in 1~5×10 4 CFU / mL bacterial concentration environment was cultured in a shaker at 24±1℃ and 150rpm for 18h, and then diluted into bacterial suspensions of different multiples, and then poured into agar medium and cultured at 37±1℃ for 24-48h. The antibacterial activity of the sample was quantitatively evaluated using the following formula: Where W t (CFU / mL) is the average concentration of viable bacteria in three identical control samples after 18 h, Q t (CFU / mL) is the average concentration of viable bacteria in three identical control samples after 18 h.
[0061] 6. Testing method of blood coagulation index BCI
[0062] First, all samples and hemostatic gauze (1cm×1cm×0.15cm) were placed on a twelve-well culture plate, preheated at 37°C for 5 minutes, and then 100μL of fresh anticoagulated rabbit blood was added. Subsequently, 10μL of CaCl2 solution was dripped into the mixture and reacted for 5 minutes (37°C). 25mL of deionized water was dripped into the 12-well culture plate, collected with a centrifuge tube, and the non-agglomerated red blood cells were washed, shaken at 30rpm for 10 minutes (37°C), and finally the absorbance of the washing solution containing hemoglobin was measured with an enzyme marker (540nm). For the negative control group, 100μL of anticoagulated rabbit blood was taken, and 10μL of CaCl2 was dissolved in 25mL PBS. BCI calculation formula: Where B1 and B2 are the absorbance of the sample group and the negative control group, respectively.
[0063] 7. Blood compatibility test methods
[0064] The hemocompatibility of different samples was evaluated by hemolysis rate. Take 5mL of fresh anticoagulated rabbit blood and 10mL of PBS for red blood cell-rich plasma, centrifuge at 5000rpm for 10min, and repeat 3 times. Mix red blood cells (RBC) with PBS at a ratio of 1:34. All samples were placed in a centrifuge tube containing 200μL RBC and 800μL PBS, incubated at 37℃ for 1h, and incubated in an oscillating incubator at 120 rpm for 1h at 37℃, then the mixture of RBC and sample was centrifuged at 5000 rpm for 5min, and finally the absorbance of the supernatant was measured with an enzyme marker (540nm). DW and PBS were used as positive and negative controls, respectively. The hemolysis rate (%) was calculated by the formula: Where A s ,,Apc and Anc have different absorbances of samples, namely deionized water and PBS.
[0065] 8. Cytocompatibility testing methods
[0066] In vitro cytocompatibility was assessed using the CCK-8 assay according to the method outlined in ISO 10993-12 2012. Briefly, all samples were sterilized under UV light for 30 min, and sterile samples were immersed in culture medium at 37 °C for 24 h to obtain 100 μg / mL extracts, which were then filtered and diluted to different concentrations. Nutrient solution without samples served as a control group. L929 fibroblasts in logarithmic growth phase were cultured at 6 × 10 3 The initial density of cells / well was seeded on a 96-well plate, with 100 μL of the extract per well. The cells were then placed in an incubator at 37°C and 5% CO2 for 24 hours. After removing the culture medium, each well was washed three times with PBS. Subsequently, culture medium containing 10% CCK-8 was added, 100 μL per well, and incubated at 37°C for 2 hours. Finally, the absorbance was quantified at 450 nm. The relative cell viability calculation formula is:
[0067]
[0068] OD test and OD control The absorbances of various samples and controls are shown respectively. These absorbances have been adjusted to remove the background absorbance, which only includes the culture medium containing 10% CCK-8.
[0069] 9. In vivo hemostasis test method
[0070] The rat liver injury model and tail-cut model were used to measure the hemostatic time and bleeding volume to determine the hemostatic performance of the hemostatic material.
[0071] All SD rats were first adapted to the environment and fed for one week. After anesthesia, the middle lobe of the liver was cut into an "X" shape (1.2 cm long ×
[0072] The hemostatic test was performed on the SD rat liver injury model (depth 0.25cm), which is the SD rat liver injury model. Another tail-cutting mode is to cut the distal 2 cm of the tail. After normal bleeding, the wound is covered with hemostatic materials to stop bleeding. The hemostatic materials include medical hemostatic cotton gauze and prepared samples. The control group does not use hemostatic materials. During the treatment process, the hemostatic time (s) and blood loss (g) (weight difference before and after blood sucking) were recorded. The experiment was recorded with photos.
[0073] SD rats were obtained from SPF (Beijing) Biotechnology Co., Ltd. All animal experiments were approved by the Experimental Animal Ethics Committee of Yanxuan Biotechnology (Hangzhou) Co., Ltd. (Permit No.: SYXK (Zhejiang) 2021-0043; Approval No.: YXSW2401157188).
[0074] Example 1
[0075] A method for preparing a flexible and stable three-layer porous hemostatic dressing based on gelatin and multi-source polysaccharide reinforced cross-linked cotton yarn fabric comprises the following steps:
[0076] (1) Using gelatin and hydroxyethyl cellulose as solutes and deionized water as solvent, heating in a water bath at 60° C. and stirring until dissolved, to prepare a mixed solution, wherein the gelatin content is 2 wt % and the hydroxyethyl cellulose content is 1.5 wt %;
[0077] (2) adding glycerol to the mixed solution obtained in step (1), and using an IKA homogenizer to stir at high speed until the solution volume foams, and the volume after foaming reaches 1.5 to 3 times of the original volume, and stopping when stability is reached to form a foaming solution A; wherein the glycerol content in solution A is 2 wt%; the high-speed stirring speed is 15K rpm, and the stirring time is 4 minutes;
[0078] (3) Carboxymethyl chitosan and sodium alginate are used as solutes in a mass ratio of 3:1, water is used as a solvent, and glycerol is added to prepare a polysaccharide solution B; wherein the total content of the polysaccharide is 2.5wt%, and the content of glycerol is 2wt%;
[0079] (4) adding polysaccharide solution B to the foaming solution A obtained in step (2), wherein the volume ratio of the foaming solution A to the polysaccharide solution B is 2:1, and obtaining a mixed solution C after high-speed stirring, and then adding tannic acid to form a mixed solution D with a content of 0.75 wt% (the content of tannic acid in the mixed solution D), and obtaining a double-layer solution after high-speed stirring, wherein the upper layer is a part rich in foam, and the lower layer is a homogeneous matrix; the speed of the above two high-speed stirrings is 15K rpm, and the stirring time is 3 minutes;
[0080] (5) ultrasonically cleaning the cotton gauze for 1 hour and then drying it, and then ultrasonically immersing it in a tannic acid solution of the same concentration as in step (4) for 1 hour and then continuing to immerse it for 24 hours. The immersed cotton gauze was spread on the inside of the lid of a culture dish and then frozen in a -80°C ultra-low temperature refrigerator for 10 minutes;
[0081] (6) Structural design of the sample: pour the lower layer of the double-layer solution of step (4) onto a culture dish, take out the frozen cotton gauze of step (5) and place it on top of it, and then pour the upper layer of the solution on top of it, forming a U (upper layer of solution)-C (cotton gauze)-L (lower layer of solution) structure (UCL) from top to bottom;
[0082] (7) The sample structure product obtained in step (6) is immediately placed in a -80°C ultra-low temperature freezer for freezing, and the obtained crystal product is freeze-dried, and the freeze-drying is vacuum freeze-drying, and the specific conditions are: temperature of -80°C, vacuum degree of 60Pa, and freeze-drying time of 36 hours; then placed in an impregnation solution for impregnation cross-linking for 5 minutes, and the composition of the impregnation solution is: an aqueous solution containing 0.1 mol / L CaCl2 and 2 wt% glycerol;
[0083] (8) The cross-linked product obtained in step (7) is washed (washed 3 times with deionized water) and freeze-dried again under the same freeze-drying conditions as step (7), thereby obtaining a flexible and stable three-layer porous hemostatic dressing based on gelatin and multi-source polysaccharide reinforced cross-linked cotton yarn fabric.
[0084] The hemostatic dressing prepared in Example 1 is characterized to be soft in texture and has a three-layer asymmetric double-network multi-source porous structure, including an upper porous structure layer, a lower porous structure layer and a middle cotton gauze layer. The pore sizes of the upper and lower porous structures and the structure of the middle cotton gauze layer are different. Figure 1 As shown in m, n, and o.
[0085] Example 2
[0086] The only difference from Example 1 is that the tannic acid content in the mixed solution D in step (4) is 0.25 wt %. The other parameters and conditions are the same as those in Example 1.
[0087] The hemostatic dressing prepared in Example 2 is characterized to be soft in texture and has a three-layer asymmetric double network multi-source porous structure. Figure 1 As shown in g, h, and i.
[0088] Example 3
[0089] The only difference from Example 1 is that the tannic acid content in the mixed solution D in step (4) is 0.5 wt %. The other parameters and conditions are the same as those in Example 1.
[0090] The hemostatic dressing prepared in Example 3 is soft in texture and has a three-layer asymmetric double network multi-source porous structure. Figure 1 As shown in j, k, and l.
[0091] Example 4
[0092] The only difference from Example 1 is that the tannic acid content in the mixed solution D in step (4) is 1 wt %. Other parameters and conditions are the same as those in Example 1.
[0093] The hemostatic dressing prepared in Example 4 is characterized to be soft in texture and has a three-layer asymmetric double network multi-source porous structure. Figure 1 As shown in p, q, and r.
[0094] Example 5
[0095] The only difference from Example 1 is that the tannic acid content in the mixed solution D in step (4) is 1.25 wt %. The other parameters and conditions are the same as those in Example 1.
[0096] The hemostatic dressing prepared in Example 5 has a three-layer asymmetric double network multi-source porous structure, such as Figure 1 As shown in s, t, and u.
[0097] Example 6
[0098] The only difference from Example 1 is that the tannic acid content in the mixed solution D in step (4) is 1.5 wt %. The other parameters and conditions are the same as those in Example 1.
[0099] The hemostatic dressing prepared in Example 6 has a three-layer asymmetric double network multi-source porous structure, such as Figure 1 As shown in v, w, and x.
[0100] Comparative Example 1
[0101] The only difference from Example 1 is that the addition of tannic acid in step (4) is omitted, and other parameters and conditions are the same as those in Example 1.
[0102] The hemostatic dressing prepared in Comparative Example 1 was characterized to be soft in texture, but with a collapsed structure and lack of multiple functions. Figure 1 d, e, and f are shown. For comparison, see Figure 2 .
[0103] Comparative Example 2
[0104] The only difference from Example 1 is that in step (6), samples with different design structures are prepared by placing frozen cotton gauze at the bottom of a culture dish and pouring the double-layer solution obtained in step (4) thereon, i.e., pouring it from top to bottom to form a ULC structure. Other parameters and conditions are the same as in Example 1.
[0105] The hemostatic dressing obtained in this comparative example has similar performance to that of Example 1, but Example 1 has a lower structure that is more close to the skin and in direct contact with the skin, and the wound is more easily degraded, that is, easier to remove after use. The hemostatic dressing prepared in Comparative Example 2 has an extremely uneven bottom of cotton gauze and poor adhesion; this is mainly due to the large difference in the bonding strength of the two sides of the cotton gauze, resulting in partial detachment of the joint. See the actual picture for comparison Figure 2 .
[0106] Comparative Example 3
[0107] The only difference from Example 1 is that the high-speed stirring and placement sequence in steps (2) and (4) are omitted, and the gelatin, hydroxyethyl cellulose, glycerol, carboxymethyl chitosan, sodium alginate and tannic acid are directly mixed together and stirred at a low speed until they are completely dispersed. The other parameters and conditions are the same as those in Example 1.
[0108] The dressing obtained in this comparative example is easy to bend and break, has a single porous structure without stratification, and has a lower porosity than Example 1, cannot achieve hierarchical hemostasis, and feels harder than Example 1.
[0109] Comparative Example 4
[0110] The only difference from Example 1 is that steps (5) and (6) are omitted, and other parameters and conditions are the same as those in Example 1.
[0111] The results show that the material prepared in the comparative example is a double-layer dressing, but the preparation method cannot achieve large-area design. In contrast, the dressing prepared in Example 1 has a better molding effect, can be designed with a large-area structure, and the sample feels relatively soft and can maintain excellent bending properties in both dry and wet states. This dressing has the best performance.
[0112] Comparative Example 5
[0113] The only difference from Example 1 is that the addition of hydroxyethyl cellulose is omitted in step (1), and the other parameters and conditions are the same as those in Example 1.
[0114] In the preparation process of this comparative example, in step (4), the double-layer solution cannot be kept stable for a long time, thus affecting the subsequent structural design.
[0115] Performance Testing
[0116] 1. The porosity of the hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 was measured. The results are shown in Table 1:
[0117] Table 1. Density and porosity test results of dressing samples
[0118]
[0119] 2. The water vapor transmission rates of the hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 were measured. The results are shown in Table 2:
[0120] Table 2. Water vapor transmission rate test results
[0121]
[0122] From the results in Table 2, it can be seen that except for the water vapor permeability of the samples prepared in Comparative Example 1, which is at 2700 g / m 2 / day, the water vapor permeability of the medical hemostatic dressings prepared in Examples 1 to 6 is in the range of 2900 to 3050 g / m 2 / day, which is beneficial for wound recovery.
[0123] 3. The in vitro degradation performance of the hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 was measured. The results are shown in Table 3:
[0124] Table 3 In vitro degradation test results
[0125]
[0126]
[0127] From the results in Table 3, it can be seen that the one-day degradation rates of all samples are higher than 31%, and the 21-day degradation rates of the medical hemostatic dressings prepared in Examples 1 to 6 are higher than 44%. The main degradable part is the porous structure. Although the porous structure helps to improve the degradation rate, when the tannic acid content is high, it will have a certain effect on the degradation rate. However, this also proves that tannic acid promotes the combination with protein and polysaccharide-based materials and promotes the structural integrity of the hemostatic dressing.
[0128] 4. The antioxidant properties of the hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 were measured. The results are shown in Table 4:
[0129] Table 4 Antioxidant test results
[0130]
[0131] It can be seen from the results in Table 4 that the anti-oxidation rate of the medical hemostatic dressing sample prepared in Example 1 can reach more than 80% for 30 minutes and more than 85% for 2 hours after being soaked for 2 hours; with the increase of tannic acid content, the increase of soaking time is conducive to the improvement of antioxidant effect and the acceleration of reaction saturation rate. With the increase of immersion time and reaction time, the antioxidant rate increases accordingly. There is little difference between the reaction time of 30 minutes and 2 hours in Examples 4, 5, and 6; the hemostatic dressing prepared in Comparative Example 1 has no antioxidant rate because there is no addition of tannic acid. In general, as the amount of tannic acid added gradually increases, it helps to promote instantaneous rapid antioxidant properties. At the same time, the porous structure promotes the release of tannic acid in a short time, thereby further improving the immediate antioxidant properties of the hemostatic dressing.
[0132] 5. The antibacterial properties of the hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 were measured. The results are shown in Table 5:
[0133] Table 5 Antibacterial test results
[0134]
[0135]
[0136] As shown in Table 5, within 18 hours, the antibacterial rates of the dressings prepared in Examples 1 to 6 against Staphylococcus aureus can reach more than 76%, and the antibacterial rates against Escherichia coli can reach 59% and above. The antibacterial effect is significantly improved with the increase of the amount of tannic acid added. This proves that the addition of tannic acid is the key to obtaining excellent antibacterial properties. The porous structure also helps to promote the release of tannic acid, thereby further improving the antibacterial effect of the dressing.
[0137] 6. The hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 were subjected to the blood coagulation index BCI test. The results are shown in Table 6:
[0138] Table 6 Coagulation index BCI (5min) test results
[0139]
[0140] Results As shown in Table 6, the BCI of the upper porous structure and the lower porous structure of the dressings prepared in Examples 1 to 6 were both lower than 28%, and the prepared dressings all had a three-layer structure with different BCI values, and the coagulation index of each layer had a certain difference, which could achieve a rapid hierarchical hemostasis effect when in contact with the wound; however, blood penetrated layer by layer, and the BCI of the middle cotton gauze layer was slightly higher than that of the outer two sides, but the stable and easily absorbent structural network of the cotton gauze itself helped the blood to diffuse stably and evenly in the layer, and the blood was stored in the layer, which not only effectively and quickly stopped bleeding, but also avoided excessive adsorption of blood and tissue fluid to condense in the skin-approaching layer to cause the wound to dry and crack; that is, it could effectively control wound bleeding, quickly absorb blood and tissue fluid around the wound, and effectively maintain the humidity of the wound; the outer porous structure could absorb and store blood and tissue fluid to reduce the number of dressing changes, thereby reducing damage to the new granulation tissue in the wound; it could quickly and effectively inhibit wound bleeding, quickly absorb blood and tissue fluid around the wound, and at the same time maintain a suitable humidity of the wound, which was beneficial to wound recovery; the excipients prepared by the present invention were significantly superior to commercially available hemostatic gauze and commercially available gelatin hemostatic sponge.
[0141] 7. The blood compatibility of the hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 was measured. The results are shown in Table 7:
[0142] Table 7 Blood compatibility test results
[0143]
[0144] From the results in Table 7, it can be seen that the hemolysis rates of all samples are lower than the critical safety range of hemolysis (5%), and all samples have good blood safety.
[0145] 8. The hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 were subjected to cytocompatibility tests. The results are shown in Table 8:
[0146] Table 8 Cell compatibility test results
[0147]
[0148] From the results in Table 8, it can be seen that the cell survival rates of all samples are above 85%, indicating that the samples have good biosafety.
[0149] 9. The hemostatic dressings prepared in Examples 1 to 6 and Comparative Example 1 were tested for in vivo hemostasis. The results are shown in Table 9:
[0150] Table 9 In vivo hemostasis test results
[0151]
[0152]
[0153] From the results in Table 9, it can be seen that the dressing prepared in Example 1 has faster hemostasis ability and less bleeding.
[0154] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a flexible and stable three-layer porous hemostatic dressing, characterized in that: The preparation method comprises the following steps: (1) preparing a mixed aqueous solution using protein substances and cellulose derivative substances as solutes and water as solvent; (2) adding glycerol to the mixed aqueous solution obtained in step (1), stirring at high speed until the volume of the solution foams, and the volume after foaming reaches 1.5 to 3 times of the original volume, and stopping when stability is reached, thereby forming a foaming solution A; (3) using a polysaccharide-based matrix material as a solute, water as a solvent, and adding glycerol to prepare solution B; (4) adding the solution B of step (3) to the foaming solution A obtained in step (2) to obtain a mixed solution C, stirring at high speed, and then adding tannic acid to form a mixed solution D, and continuing to stir at high speed to obtain a double-layer solution; (5) Product structure design: Pour the lower layer of the double-layer solution in step (4) onto a culture dish, then spread the cotton gauze on it, and then pour the upper layer of the double-layer solution in step (4) onto the cotton gauze to form a top-down UCL structure product; (6) freezing the UCL structure product obtained in step (5) immediately, freeze-drying it, and then placing it in an impregnation solution for impregnation cross-linking; (7) The cross-linked product obtained in step (6) is washed and freeze-dried again to obtain a flexible and stable three-layer porous hemostatic dressing.
2. The preparation method according to claim 1, characterized in that: The protein material in step (1) includes one or more of egg white, gelatin, collagen, and protein powder; the cellulose derivatives include one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
3. The preparation method according to claim 1, characterized in that: The mass concentrations of proteins and cellulose derivatives in the mixed aqueous solution of step (1) are 0.5wt% to 5wt% and 0.5wt% to 5wt%, respectively.
4. The preparation method according to claim 1, characterized in that: The glycerol content in the solution A in step (2) is 0.1 to 5 wt%.
5. The preparation method according to claim 1, characterized in that: The high-speed stirring speed of step (2) is 0.5 to 15K rpm, and the time is 1 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: The polysaccharide-based matrix material in step (3) includes one or more of chitin, chitosan, carboxymethyl chitosan, cellulose, sodium carboxymethyl cellulose, sodium alginate, starch, agar, pectin and gum, and glycosaminoglycan.
7. The preparation method according to claim 1, characterized in that: The polysaccharide content in solution B of step (3) is 1 wt% to 5 wt%; and the glycerol content is 0.1 to 5 wt%.
8. The preparation method according to claim 1, characterized in that: The concentration of tannic acid added to solution D in step (4) is 0 to 1.5 wt %.
9. The preparation method according to claim 1, characterized in that: In step (4), the volume ratio of the foaming solution A to the solution B is 3:1 to 1:
3.
10. A flexible and stable three-layer porous hemostatic dressing prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Rapid hemostatic sponge and preparation method thereof
CN114569783A
Preparation method and application of self-healing antibacterial pain-relieving gelatin hydrogel wound dressing
CN116459388A
Hemostatic gauze and preparation method thereof
CN118079062A
Cited By
Dressing with cooling and moisture conducting capabilities and preparation method thereof
CN120837705A